Fault-tolerant cycle embedding in dual-cube with node faults. (29th September 2005) - Li, Yamin; Peng, Shietung; Chu, Wanming
A low-degree dual-cube was proposed as an alternative to the hypercubes. A dual-cube DC(m) has m + 1 links per node, where m is the degree of a cluster (m-cube) and one more link is used for connecting to a node in another cluster. There are 2 m+1 clusters and hence the total number of nodes in a DC(m) is 2 2m+1 . In this paper, by using Gray code, we show that there exists a fault-free cycle containing at least 2 2m+1 –2f nodes in DC(m), m≥3, with f≤m faulty nodes.